Cassava Starch: Structural Modification for Development of a Bio-Adsorber for Aqueous Pollutants. Characterization and Adsorption Studies on Methylene Blue - Guarda-Moraga, A; Romero-Figueroa, J; Galotto-Lopez, M (Springer Science and Business Media Deutschland GmbH, 2021)
A potential bio-adsorber of contaminants in aqueous medium was developed in this work through modified starches using organic acids. Methylene blue (MB) was used as example of a pollutant agent. For this purpose, firstly three types of modified starches were prepared using malonic, glutaric, and valeric acids in aqueous solution at different concentrations. The characterization of modified starches showed concordance with the chemical structure of the acid incorporated in starch. Pseudo-second-order model explains the rate of adsorption of the cationic dye MB. The adsorption of MB was carried out through intraparticle diffusion mechanism mainly. Physical and chemical interactions between modified starch and MB are involved. © 2020, Springer-Verlag GmbH Germany, part of Springer Nature.